Assessment of Value Additions in Afforestation Works - Paul Raj, S. (Indian Forester, 1998)
In the Forest Department so far no qualified analytical method to evaluate afforestation works is available. This is the first attempt to evaluate the afforestation works by identifying all the values obtained. The relative importance of each value is discussed with reference to particular afforestation works. This will help to understand which value should be given priority in any afforestation works according to the object of management. The methodology will pave way to further thinking on this issue so as to bring out still refined methods.